Yes we (still) can politics in the age of Obama, Twitter, and Trump - Pfeiffer, Dan (New York Twelve, an imprint of Grand Central Publishing, 2018)
"From Obama's former communications director and current co-host of Pod Save America comes a colorful account of how politics, the media, and the Internet changed during the Obama presidency and how Democrats can fight back in the Trump era. On November 9th, 2016, Dan Pfeiffer woke up like most of the world wondering WTF just happened. How had Donald Trump won the White House? How was it that a decent and thoughtful president had been succeeded by a buffoonish reality star, and what do we do now? Instead of throwing away his phone and moving to another country (which were his first and second thoughts), Pfeiffer decided to tell this surreal story, recounting how Barack Obama navigated the insane political forces that created Trump, explaining why everyone got 2016 wrong, and offering a path for where Democrats go from here. Pfeiffer was one of Obama's first hires when he decided to run for president, and was at his side through two presidential campaigns and six years in the White House. Using never-before-heard stories and behind-the-scenes anecdotes, Pfeiffer examines how Obama succeeded despite Twitter trolls, Fox News (and their fake news), and a Republican Party that lost its collective mind. An irreverent, no-BS take on the crazy politics of our time."--
Introduction: If you're reading this, it's too late -- Started from the bottom -- How not to lose a campaign -- Telling the country and other tales of presidential communications -- Something pants-splittingly funny -- The new media wasteland -- Fighting fake news -- My beautiful, dark, twisted (White House) fantasy -- Fox (and Friends) is destroying America -- The Republicans go off the deep end -- Tweeting while Rome burns -- From 1600 Penn to Keepin' it 1600 -- Advice you can believe in -- The 2016 campaign clusterfuck -- Thanks, Obama (seriously)
Includes bibliographical references
1
Keywords: Obama, Barack; Pfeiffer, Dan; Trump, Donald -- 1946-; Presidents -- United States -- Staff -- Biography; United States -- Politics and government -- 2009-2017; United States -- Politics and government -- 2017-